Mechanistic Insights into Binding of Ligands with Thiazolidinedione Warhead to Human Histone Deacetylase 4 - Markus Schweipert; Niklas Jänsch; Neha Upadhyay; Kalpana Tilekar; Ewelina Wozny; Sidra Basheer; Eva Wurster; Marlene Müller; Ramaa C S; Franz-Josef (MDPI AG, 2021)
Recently, we have reported that non-hydroxamate thiazolidinedione (TZD) analogs are capable of inhibiting human deacetylase 4 (HDAC4). This study aims at the dissection of the molecular determinants and kinetics of the molecular recognition of TZD ligands by HDAC4. For this purpose, a structure activity relationship analysis of 225 analogs was combined with a comprehensive study of the enzyme and binding kinetics of a variety of HDAC4 mutant variants. The experimental data were rationalized by docking to the two major conformations of HDAC4. TZD ligands are competitive inhibitors and bind via a two-step mechanism involving principal molecular recognition and induced fit. The residence time of 24 g is (34 ± 3) min and thus much larger than that of the canonical pan-HDAC inhibitor SAHA ((5 ± 2) min). Importantly, the binding kinetics can be tuned by varying the structure of the CAP group.